The Need to Improve the Competency of School Administrators Under The Educational Opportunity Expansion Schools Under The Saraburi Primary Educational Service Area Office - Niruttinanont , phongphich; Chucheep, Sunchai; Hankla, Chalearmchai (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The purposes of this research were to 1) Study the current and desirable conditions of the competency of the school administrator under The Educational Opportunity Expansion Schools under the Saraburi Primary Educational Service Area Office 2) Analyze the necessary needs of the competency of school administrators under The Educational Opportunity Expansion Schools under the Saraburi Primary Educational Service Area Office and 3) Propose ways to improve the competency of school administrators under The Educational Opportunity Expansion Schools under the Saraburi Primary Educational Service Area Office. The 292 samples of school administrators and teachers under the Saraburi Primary Educational Service Area Office in academic year 2021 were calculated by Yamane’s formula and stratified random sampling by school size. The proportion of school administrators and teachers was 15:85 percent. The research instrument were: the current condition questionnaires with a reliability value of 0.988, the desirable conditions questionnaires with a reliability value of 0.978 and semi-structured interview. Data were analyzed in terms of percentage, average, standard deviation, PNI Modified and content analysis. The results showed that: 1. The current conditions and the desirable conditions of the competency of the school administrator under The Educational Opportunity Expansion Schools under the Saraburi Primary Educational Service Area Office were rated at highest level and the high, respectively. 2. Order of the necessary needs of the competency of school administrators under The Educational Opportunity Expansion Schools under the Saraburi Primary Educational Service Area Office: The first core competency was achieved and the first functional competency were critical thinking and synthesis. And 3. Guidelines for the development of competency of school administrators under The Educational Opportunity Expansion Schools Under the Saraburi Primary Educational Service Area Office, all 8 competencies have procedures and processes that can be applied to all competencies.